1996
DOI: 10.1002/(sici)1096-9896(199606)179:2<151::aid-path556>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the Von Hippel-Lindau Tumour Suppressor Gene in Capillary Haemangioblastomas of the Central Nervous System

Abstract: A series of 20 capillary haemangioblastomas of the central nervous system was screened for mutations of the von Hippel–Lindau (VHL) tumour suppressor gene by single strand conformational polymorphism (SSCP) and heteroduplex analysis. Aberrant polymerase chain reaction (PCR) products were detected in ten tumours. DNA sequencing of these PCR products revealed that seven tumours had frameshift mutations due either to deletions of one or more base pairs (six cases) or to insertion of one base pair (one case). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…Oberstrass et al [1996] found 50% (10/20) sporadic CNS hemangioblastomas had VHL mutations: 7 were somatic mutations (35%), 2 were germline (10%), and 1 was not determined. These VHL mutations included seven frameshifts, two splices, and one missense mutation [Oberstrass et al, 1996]. Lee et al [1998] found 52.6% of 19 screened sporadic cerebellar hemangioblastomas had 3p25 allelic deletion.…”
Section: Sporadic Hemangioblastomasmentioning
confidence: 99%
See 2 more Smart Citations
“…Oberstrass et al [1996] found 50% (10/20) sporadic CNS hemangioblastomas had VHL mutations: 7 were somatic mutations (35%), 2 were germline (10%), and 1 was not determined. These VHL mutations included seven frameshifts, two splices, and one missense mutation [Oberstrass et al, 1996]. Lee et al [1998] found 52.6% of 19 screened sporadic cerebellar hemangioblastomas had 3p25 allelic deletion.…”
Section: Sporadic Hemangioblastomasmentioning
confidence: 99%
“…Similarly, sporadic RCC in patients exposed to the industrial solvent trichloroethylene (TCE) display similar histopathological features and also harbor VHL mutations [Brauch, 2004;Brüning et al, 1997;Charbotel et al, 2007;Shiao, 2009;Wells et al, 2009]. Somatic VHL mutations are commonly involved in the tumorigenesis of hemangioblastomas, accounting for up to 50% of sporadic retinal and CNS hemangioblastomas [Maher et al, 1990a;Neumann et al, 1989;Oberstrass et al, 1996;Richard et al, 1998]. Interestingly, sporadic pheochromocytoma are rarely (3%) due to somatic VHL mutations [Bar et al, 1997;Eng et al, 1995;Glasker et al, 2001;Neumann et al, 1993;Sprenger et al, 2001].…”
Section: Sporadic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the majority of sporadic and hereditary (VHL diseaseassociated) ccRCC lacks functional VHL due to loss or mutation of the VHL gene. VHL loss is also associated with sporadic cerebellar haemangioblastomas with prevalence between 25-50% [9,10]. VHL À/À mice die in utero due to defective placental dysgenesis [11], but targeted cell specific suppression of VHL is possible.…”
Section: Vhl and Sporadic Cancermentioning
confidence: 99%
“…Germ-line mutation confers genetic risk of tumor formation in concert with somatic second VHL allele loss or DNA methylation inactivation. However, somatic loss or inactivation of the wild-type vhl allele has been demonstrated in central nervous system (CNS) sporadic hemangioblastomas (Gnarra JR et al, 1994;Kanno H et al, 2000;Foster K et al, 1994;Herman JG et al 1994;Oberstrass J, et al, 1996;Tse J et al, 1997;Lee J-Y et al, 1998), in sporadic and VHL-associated renal cell carcinomas (RCCs) (Latif F et al, 1993;Shuin T et al, 1994;Phillips JL et al, 2001), pheochromocytoma (Bender BU et al, 2000;Linehan WM et al, 2001) and in endolymphatic sac tumors (ELSTs) (Vortmeyer AO et al, 2000).…”
Section: Molecular Genetics Of Vhl Diseasementioning
confidence: 99%